Hubungan Pendampingan Suami terhadap Tingkat Kecemasan Ibu Bersalin Kala I di Wilayah Kerja Puskesmas Semowo - Hartini Hartini; Shinta Lia Nana Mardiyana (Jurnal Sains dan Kesehatan, 2026)
Emotional distress frequently manifests during the primary stages of labor, potentially obstructing a seamless delivery process. Maintaining the husband's proximity to the mother is perceived as a vital psychological anchor to alleviate such distress. This investigation aims to evaluate the nexus between spousal involvement and the intensity of anxiety among mothers in the first stage of labor at Semowo Health Center. Employing an observational analytical framework with a cross-sectional approach, 33 participants were recruited via total sampling. Anxiety assessment utilized the HARS scale, with data subsequently processed through Chi-square analysis. The results demonstrated that most unassisted mothers experienced high-level anxiety (55.6%). Conversely, 45.8% of those with spousal accompaniment exhibited only moderate anxiety levels. A significant correlation was established between husband assistance and maternal emotional states in the Semowo region (p-value = 0.029). Consequently, active husband participation proves essential in mitigating labor-related anxiety and warrants stronger emphasis within maternal healthcare protocols